TEACHER’S QUESTIONS IN ENGLISH CLASSROOM INTERACTION AT SMA NEGERI 1 BABALAN - Andika Pratama; Rahmad Husein; Willem Saragih (Universitas Negeri Medan, 2017)
This qualitative study was aimed at investigating the kinds of question which were raised by an English teacher with respect to cognitive level in the classroom. The data were obtained by an audio-recording and the transcription of the teacher’s questions in meeting of English subject. The English teacher and his forty students were involved as the participant in the classroom interaction. The kinds of question were identified by using Revised Bloom Taxonomy’s Theory proposed by Forehand (2005). The findings of this research show that the English teacher had applied his questions with respect to the five out of six from cognitive levels; they are Remembering, Understanding, Applying, Analyzing, and Evaluating. As the result of analysis, the percentage of kinds of questions with respect to understanding level is 32%(8 questions). Then, the analyzing level is 28%(7 questions), the remembering level is 16% (4 questions), the applying level is 12%(3 questions), and the evaluating level is 12% (3 questions).Furthermore, the understanding level is the most raised by the English teacher which means that the level explicitly explains that the questions used by the teacher are still categorized to the basic skill. In relation to that, it is concluded that the level indicated that all the teacher’s questions transcribed with respect to the five of cognitive levels do not fulfill as category in organizing the questions well in classroom interaction. And the level would only aim to elicit factual answers, recognize information from interpreting the meaning and check student’s comprehension. Keywords: Classroom Interaction, Teacher’s Questions, Kinds of Teacher Questions with Respect to the Cognitive Domain